Autophagy Activation Promoted by Pulses of Light and Phytochemicals Counteracting Oxidative Stress during Age-Related Macular Degeneration - Roberto Pinelli; Michela Ferrucci; Francesca Biagioni; Caterina Berti; Violet Vakunseth Bumah; Carla Letizia Busceti; Stefano Puglisi-Allegra; Gloria Lazzeri; Alessandro Frati; Francesco Fornai (MDPI AG, 2023)
The seminal role of autophagy during age-related macular degeneration (AMD) lies in the clearance of a number of reactive oxidative species that generate dysfunctional mitochondria. In fact, reactive oxygen species (ROS) in the retina generate misfolded proteins, alter lipids and sugars composition, disrupt DNA integrity, damage cell organelles and produce retinal inclusions while causing AMD. This explains why autophagy in the retinal pigment epithelium (RPE), mostly at the macular level, is essential in AMD and even in baseline conditions to provide a powerful and fast replacement of oxidized molecules and ROS-damaged mitochondria. When autophagy is impaired within RPE, the deleterious effects of ROS, which are produced in excess also during baseline conditions, are no longer counteracted, and retinal degeneration may occur. Within RPE, autophagy can be induced by various stimuli, such as light and naturally occurring phytochemicals. Light and phytochemicals, in turn, may synergize to enhance autophagy. This may explain the beneficial effects of light pulses combined with phytochemicals both in improving retinal structure and visual acuity. The ability of light to activate some phytochemicals may further extend such a synergism during retinal degeneration. In this way, photosensitive natural compounds may produce light-dependent beneficial antioxidant effects in AMD.